2009
DOI: 10.4161/oxim.2.4.8878
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Senegal Gum Exudate Offers Protection Against Cyclophosphamide‐Induced Urinary Bladder Cytotoxicity

Abstract: Cylophosphamide (CYCL) is a strong anticancer and immunosuppressive agent but its urotoxicity presents one of the major toxic effects that limit its wide usage particularly in high dose regimens. Therefore, this study aimed to investigate Acacia Senegal gum exudate, Gum Arabic (GA), for its possible role as a natural, nontoxic agent against CYCL-induced urotoxicity. Male Swiss albino rats were exposed to CYCL (150 mg/kg BW, once i.p) with or without GA oral supplementation (7.5 g/kg/day for 6 days) through dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
(62 reference statements)
1
39
0
Order By: Relevance
“…Acrolein causes the depletion of cellular antioxidant nucleophiles, such as glutathione, and it initiates the lipid peroxidation that results in HC [39]. Scientists have demonstrated a severe depletion in cellular GSH content in urinary bladder homogenates of CPtreated groups [25,40]. IFO caused significant reductions in GSH levels both in kidney and bladder, when compared Images presented in column A were stained with HxE.…”
Section: Discussionmentioning
confidence: 97%
“…Acrolein causes the depletion of cellular antioxidant nucleophiles, such as glutathione, and it initiates the lipid peroxidation that results in HC [39]. Scientists have demonstrated a severe depletion in cellular GSH content in urinary bladder homogenates of CPtreated groups [25,40]. IFO caused significant reductions in GSH levels both in kidney and bladder, when compared Images presented in column A were stained with HxE.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the increase in MDA and NO(x) levels along with the decreased GSH contents, might be due to the ability of acrolein to deprive the cell of its natural defense (GSH) against the ROS (Al-Yahya et al, 2009) or to the direct conjugation of CP and its metabolites with free or protein bound SH groups (Yousefipour et al, 2005), stimulating the formation of free radicals thereby interfering with the antioxidant functions (Al-Yahya et al, 2009;Tsakadze et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…It is also used to treat some non-cancerous conditions (Al-Yahya et al, 2009). CP used in regimen prior to stem cell transplantation and in low doses in the treatment of several autoimmune diseases (Luznik and Fuchs, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[192021] In an actively sensitized animal model, Zhu et al . [9] demonstrated that nebulized ketamine decreased IL-4 and NO levels and the expression of i-NOS in the inflamed airways and, as a result, ketamin-attenuated airway hyperresponsiveness and inflammation in experimental asthma.…”
Section: Discussionmentioning
confidence: 99%